Evaluating The Models of Sharia Microfinance in Indonesia: an Analytical Network Process (ANP) Approach - Amalia, Euis; Atiqah, Mahmudah (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2015)
This study focuses on evaluating the  performances  of  three  sharia  microfinance  models,  i.e.  cooperative  model represented by BMT al Fath, Grameen model represented by MBK, Ltd.co, and mixed model represented by Baytul Amanah Ikhtiar cooperative. ANP approach is used to evaluate the performances of those models from five important aspects (clusters)  as  the  determiners,  such  as  human  resource,  finance,  management, sharia  compliance,  and  marketing.  The  findings  of  this  research  show  that  the most important aspect (priority) among the clusters is human resource. Thus, the best strategy is the mixed-based; the model which integrates the cooperative system with grameen system. It becomes the best model inasmuch as it implements values of  both  co  ownership  and  co  responsibility,  in  addition  to  power  of  collectivity resulting in no cash collateral.DOI:10.15408/aiq.v7i1.1355